2007
DOI: 10.1562/0031-8655(2003)0770556piotdt2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of the Dermatophyte Trichophyton rubrum¶

Abstract: Dermatophytes are fungi that can cause infections (known as tinea) of the skin, hair and nails because of their ability to use keratin. Superficial mycoses are probably the most prevalent of infectious diseases worldwide. One of the most distinct limitations of the current therapeutic options is the recurrence of the infection and duration of treatment. The present study shows that Trichophyton rubrum in suspension culture is susceptible to photodynamic treatment (PDT), a completely new application in this are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 11 publications
2
37
0
2
Order By: Relevance
“…Growth inhibition was achieved with thiophenes 2. (41). Our findings show that PEI-ce6 can be used for photoinactivation of C. neoformans.…”
Section: Resultsmentioning
confidence: 66%
“…Growth inhibition was achieved with thiophenes 2. (41). Our findings show that PEI-ce6 can be used for photoinactivation of C. neoformans.…”
Section: Resultsmentioning
confidence: 66%
“…Pc 4-PDT also demonstrated an excellent safety profile in a phase 1 trial on cutaneous neoplasms (25). Although the susceptibility of T. rubrum to PDT using other photosensitizers has been extensively investigated in vitro, the mechanism of phototoxicity has not been clearly defined (2,9,(26)(27)(28). In this study, we showed that a common dose of Pc 4-PDT can induce cell death in microconidia (terbinafine-sensitive and -resistant strains of T. rubrum).…”
mentioning
confidence: 78%
“…Recently, the antimicrobial efficacy of PDT with endogenous porphyrins was highlighted in reports that found it to be effective against bacteria, virus, fungi, and protozoa [5,[12][13][14][15][16][17]. Thus, in this study, we attempted to treat recalcitrant Malassezia folliculitis with MAL-PDT.…”
Section: Discussionmentioning
confidence: 99%